The Chevalier de Montmagny : First Governor of New France. - Dube, Jean-Claude (Collection Amérique française, 2005)
In The Chevalier de Montmagny, Jean-Claude Dubé documents the extraordinary career of Charles Huault de Montmagny, first governor of the colony of New France. Born in Paris in 1601, and educated by the Jesuits, Montmagny studied law at the Université d'Orléans, joined the Order of Malta, and enjoyed a colourful career as a Hospitalier privateer in the Mediterranean, before arriving in New France in the spring of 1636. While Montmagny wasted little time in applying the experience he gained fighting the Ottoman Turks to New France's disputes with the Iroquois, he has also been credited with playi.